Pre-extension demonstration of Miju: a newly released bread wheat variety at highland districts of Guji Zone, Oromia Regional State Government, Ethiopia - Korji Dembi; Kebede Basha; Amare Girma; Bobo Tekle (Discover Agriculture)
Abstract Highland parts of Guji zone have potential for wheat production. However, production and productivity of the crop is very low due to limited access to improved varieties. To improve productivity of the crop, a new variety of bread wheat named Miju was released, having high yielding potential and moderately resistance to yellow, leaf and stem rusts. This study was conducted to evaluate yield performance of Miju under farmers’ field conditions, evaluate economic efficiency, create awareness and assess farmers’ feedback. Bore and Ana Sora districts and 2 kebeles from each district selected upon potentiality. Fifteen gender inclusive farmers established as FRG at each experimental location among 3 experimental farmers nominated under whom FRG reorganized in to 3 sub-groups of 5 members each. Two FTC were also selected as experimental sites where 2 FRG were established. Consequently, 14 experimental sites were used and involved a total of 90 farmers. The experimental materials were sown with row planting method on Single Block Design. The plot size of experimental units was 10 m × 10 m and 0.2 m spacing between rows. The seed drilled by hand at the rate of 150 kg ha−1 and rate of 100 kg ha−1 NPS and 50 kg ha−1 N. Training and field day were organized. Quantitative data analyzed using independent T-test. Farmers’ preference criteria were analyzed using Likert scale whereas farmers’ feedback was by qualitative content analysis. Profitability of the new variety was analyzed using incremental benefit cost ratio formula. An average yield of 30.132 and 25.307 quintals ha−1 was obtained from Miju and Hulluka varieties respectively. The Miju revealed a yield advantage of 19.07% and incremental benefit cost ratio of 215.026 over standard check. Based on attributes like yield, disease resistance, market demand, tiller capacity and spike length farmers ranked Miju variety first. Therefore, recommended for up scaling.